Interventions for achieving sustainability in tropical forest and agricultural landscapes - Newton, Peter; Agrawal, Arun; Wollenberg, Eva Karoline (International Food Policy Research Institute, 2013)
The rapid expansion of commodity agriculture in tropical forest landscapes is a key driver of deforestation. To meet the growing demand from a more prosperous and expanding global population, it is imperative to develop sustainable commodity supply chains that support higher agricultural productivity, and that enable improved environmental, economic, and social outcomes. Interventions by community, market, and state actors can enhance the sustainability of supply chains by affecting where and how agricultural production occurs. These interventions—in the form of novel or moderated institutions and policies, incentives, or information—can influence producers directly or achieve their impacts indirectly by influencing consumer, retailer, and processor decisions. Global datasets were used to document the trends in deforestation and commodity agriculture production and a framework was developed to facilitate analyses of commodity supply chains across multiple interventions, commodities, and countries. The framework can be used to compare and explain the impacts of different types of supply chain interventions. The paper demonstrates how the framework can be used by generating hypotheses about decisions and choices of different actors and likely effects on commodity agriculture expansion.